Gallstone ileus: passage duodenal fistula suture - Latourrette, Federico (Cirugía del Uruguay, 2020)
1) A case of gall stone intestinal obstruction is reported. Biliary pneumatosis was the clue for a corre.et pre-operative diagnosis. 2) During surgical exploration division of colecystoduodenal adhesions demonstrate a duodenal fistula. 3) Duodenal surgical suture -in two layers- was satisfactory.